Rancangan Antena Penerima Automatic Dependent Surveillance Broadcast dengan Frekuensi 1090 Mhz Menggunakan RTL820T - Azis, Abdul; Setiawan, Rio (Politeknik Penerbangan Makassar, 2019)
Introduction and learning about navigation equipment ADS-B was very important to increase the knowledge of cadet of CASEA Makassar about how ADS-B works and its display on the monitor. The purposed of this design was to produce a design that would display the interface of ADS-B in real time as a media to increase knowledge, prove that RADAR is not the only equipment thatt could determine the position of an aircraft but there was also another equipment called ADS-B. Using RTL1090 application and Virtual Radar Server, which was installed in a PC/laptop, made this design. It also uses USB shaped RTL820T module as receiver. The result of this design was that cadet could learn the display of ADS-B on the PC/laptop monitor screen which was available in the classroom or laboratory even though it’s not as real as the original ADS-B, this design could display the surveillance system that was not very different from the real or original one.